2021
DOI: 10.3389/fendo.2021.684220
|View full text |Cite
|
Sign up to set email alerts
|

Liver Proteome Profile of Growth Restricted and Appropriately Grown Newborn Wistar Rats Associated With Maternal Undernutrition

Abstract: BackgroundFetal growth restriction (FGR) has been associated with adverse perinatal outcomes and epigenetic modifications that impact gene expression leading to permanent changes of fetal metabolic pathways and thereby influence development of disease in childhood and adult life. In this study, we investigated the result of maternal food restriction on liver protein expression in Wistar male newborn pups.Materials & MethodsTen (n = 10) timed pregnant Wistar rats on their 14th day of gestation were rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Moreover, in accordance with our pathway analysis indicating an upregulation of transcriptional activity related to beta-oxidation of fatty acids, studies in rats have indicated that IUGR increased hepatic Prkaa2 expression, a subunit of AMP-activated protein kinase (a master regulator of mitochondrial beta-oxidation) ( Shen, Zhu, and Du, 2022 ). Furthermore, proteomic studies in rat hepatic tissues have demonstrated a marked enrichment of pathways related to beta-oxidation ( Sarli et al, 2021 ). Collectively, these different studies indicate a remarkably conserved response across multiple mammalian species, whereby IUGR redirects pyruvate metabolism away from the citric acid cycle and toward gluconeogenesis, as well as promoting the oxidation of fatty acids as an energy source, likely an adaption to nutrient scarcity in the intra-uterine environment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in accordance with our pathway analysis indicating an upregulation of transcriptional activity related to beta-oxidation of fatty acids, studies in rats have indicated that IUGR increased hepatic Prkaa2 expression, a subunit of AMP-activated protein kinase (a master regulator of mitochondrial beta-oxidation) ( Shen, Zhu, and Du, 2022 ). Furthermore, proteomic studies in rat hepatic tissues have demonstrated a marked enrichment of pathways related to beta-oxidation ( Sarli et al, 2021 ). Collectively, these different studies indicate a remarkably conserved response across multiple mammalian species, whereby IUGR redirects pyruvate metabolism away from the citric acid cycle and toward gluconeogenesis, as well as promoting the oxidation of fatty acids as an energy source, likely an adaption to nutrient scarcity in the intra-uterine environment.…”
Section: Discussionmentioning
confidence: 99%
“…In the liver of growth-restricted male offspring, elevated levels of triglycerides along with increased protein expression levels of lipoprotein lipase (LPL) were explained by an increase in the hepatic expression levels of liver X receptors (LXRs)-α expression that binds to the putative response elements in the LPL promoter regions (Zhu et al, 2016). In the same way, Wistar rats born to dams fed with 50% restricted diet showed induction of cholesterol biosynthesis with higher concentrations of very-low-density lipoprotein (VLDL) and lowdensity lipoprotein (LDL), lipoproteins, and triglycerides (Sarli et al, 2021). Therefore, abnormalities in adipose tissue and liver lead to dyslipidemia with metabolic consequences.…”
Section: Fetal Programming In Rodent Models Of Dietary Interventions ...mentioning
confidence: 99%
“…Therefore, a complete picture of cellular activity cannot be determined from the transcriptome alone. Recent studies connect the proteome to immune dysregulation and obesity ( Garrison et al, 2017 ) and traits relevant to the DOHaD hypothesis ( Sarli et al, 2021 ). Moreover, the proteome is known to respond to environmental stimuli ( Koga et al, 2011 ; Calamini and Morimoto, 2012 ) including diet ( Vileigas et al, 2019 ), chemical exposure ( Lee et al, 2018 ) and smoking ( Sinha et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%